2012
DOI: 10.1177/1753193412441763
|View full text |Cite
|
Sign up to set email alerts
|

The maximum distal and ulnar position of a fixed-angle volar plate to avoid intra-articular penetration

Abstract: In cases of recalcitrant carpal tunnel syndrome, many surgical procedures have been described to provide a healthy tissue bed to the median nerve, including hypothenar fat pad flaps (Strickland et al., 1996), reverse radial artery adipofascial flaps (Braun et al., 1995), pronator quadratus muscle flaps (Dautel and Merle, 1993) and abductor digiti minimi flaps (Reismann and Dellon, 1983). We report a case of the successful treatment of recalcitrant carpal tunnel syndrome by an adipofascial flap based on an uln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Nine patients had postoperative complications, three requiring plate removal for extensor tendonitis. Soong et al (2011), Gavaskar et al (2012 and Dy et al (2012) stated that flexor tendon injury is one of the most common complications of volar plate fixation of distal radial fractures. Other drawbacks of volar plate osteosynthesis include an extensive surgical approach, interruption of periosteal blood supply and risk of refracture at the end of the plate (Macintyre et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Nine patients had postoperative complications, three requiring plate removal for extensor tendonitis. Soong et al (2011), Gavaskar et al (2012 and Dy et al (2012) stated that flexor tendon injury is one of the most common complications of volar plate fixation of distal radial fractures. Other drawbacks of volar plate osteosynthesis include an extensive surgical approach, interruption of periosteal blood supply and risk of refracture at the end of the plate (Macintyre et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Using the skyline view (the wrist is flexed at 75° and forearm held 20° dorsally from the vertical axis), dorsal cortical screw penetration can be detected more sensitively and accurately than from lateral or oblique views (Riddick et al, 2012). Dy et al (2012) described in a cadaveric study that a fixed-angle volar plate could be placed distally to the watershed line without intra-articular screw penetration when using four fluoroscopic views (posteroanterior, posteroanterior with a tilt of 10°, lateral, and lateral with a tilt of 20°). On the other hand, Takemoto et al (2011) reported in their cadaveric study that using CT is superior to plain radiographs regarding screw penetration of the subchondral plate of the distal radial articular surface.…”
Section: Discussionmentioning
confidence: 99%